Students’ Background Knowledge, Vocabulary Competence, And Motivation As Predictors Of Reading Comprehension at Grade 11 Of SMA Kartika Kendari - Silvia Nasrul, Elsa; Alberth, Alberth; Ino, La (Halu Oleo University, 2019)
Reading is one of the main concerns of EFL teaching. Research shown that there are several factors contributes to reading including; background knowledge, vocabulary and motivation. Regarding the contributing factors to reading comprehension, this research set out to discover which factors partially contribute most to reading; background knowledge, vocabulary, or motivation at grade 11 of SMA Kartika XX-2 Kendari. It also evaluated the simultaneous contribution of the factors to reading comprehension grade 11 of SMA Kartika XX-2 Kendari. The objective of this study is to investigate which of the factors contributes most to reading comprehension and the simultaneous contribution of the factors to reading comprehension. This study applied quantitative study to determine the partial and simultaneous effect of the factors to reading comprehension. Using regression analysis to evaluate the contribution of the factors to reading comprehension revealed that there is a significant effect of background knowledge towards reading comprehension. It also found that there is a significant effect of vocabulary competence towards reading comprehension. While, there is no significant effect of motivation towards reading comprehension. Despite the fact that there is no significant effect of motivation towards the students’ reading comprehension, the result of multiple regression analysis on the simultaneous contribution of background knowledge, vocabulary and motivation revealed there is a simultaneous significant effect of the factors to reading comprehension